Ketertarikan Bactrocera carambolae (Diptera: Tephritidae) pada Berbagai Limbah yang Mengandung Protein - Dyah Rini Indriyanti; Edhi Martono; Andi Trisyono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2008)
There were ten processed wastes (molase, vinase, sludge, ciu, brem, tofu, milk, cacao, fish, and beer) used in these experiments. The experiments were conducted in two separated arrangements: no choice test and choice test. The no choice test was carried by testing the attractiveness of B. carambolae on each waste was compared with water. Each run consisted of four replication, for each replication consisted of 20 females and 20 males. The choice test was conducted by placing all wastes in a cage at the same time. Each run consisted of 15 replication, for each replication consisted of 100 females dan 100 males. The no choice test results showed that B. carambolae tend to visit waste more than water. The choice test results showed that B. carambolae tend to be more frequent visits to beer and cocoa waste. The content of protein inside the waste seemed to play role in attracting B. carambolae to come with.